Trust we lost: The Treuhand experience and political behavior in the former German Democratic Republic - Kim Leonie Kellermann (Westfälische Wilhelms-Universität Münster, Centrum für Interdisziplinäre Wirtschaftsforschung (CIW), 2021)
We study whether the experience of losing one's job due to the Treuhand activities in the early 1990s affected long-term political behavior among citizens of the former German Democratic Republic. During the German Reunification process, the Treuhand coordinated the privatization of former GDR firms at the cost of massive job losses. We exploit individual and spatial variation in Treuhand layoffs between 1990 and 1994, based on micro-level survey data from the German Socio-economic Panel and firm data from the IWH Treuhand Database to examine the effects on various behavioral outcomes in later years. Our results suggest that former GDR citizens who have experienced a Treuhand layoff are significantly more likely to prefer a radical party, are less interested in politics and tend to have less trust in others. At the aggregate level, districts with relatively more layoffs exhibit higher radical left vote shares in federal elections. Investigating the underlying mechanisms, we find that the effects of Treuhand job losses are relatively stronger for respondents who stayed in East Germany after Reunification. Furthermore, it seems to be nostalgia and disappointment with the transition process which drive the effects, rather than financial grievances.
Keywords: D72; E24; L33; 330; GDR; trust agency; political behavior; unemployment; radical voting